Response of tetraploid red clover to the time and method of seed grass harvesting - N. I. Kasatkina; Zh. S. Nelyubina (Аграрная наука Евро-Северо-Востока)
Timely and qualitative harvesting is an important stage of red clover seed growing. The choice of harvesting method is determined by the crop, the state of seed grass and weather conditions during the harvesting period. Field experiments were carried out in 2013-2016 on sod-podzolic medium-loamy soil of the Udmurt Republic. The seed productivity of tetraploid red clover Kudesnik in dependence on the period and method of harvesting was studied: a single-phase harvesting with the browning of 75-80% of the heads; a single-phase harvesting with the browning of 90-95% of the heads (control); desiccation during the browning of 75-80% of the heads, single-phase harvesting; two- phase harvesting with the browning of 75-80% of the heads (control); two-phase harvesting with the browning of 9095% of the heads. In conditions of cool and wet growing seasons of 2014 and 2015 the highest seed yield of tetraploid red clover Kudesnik (140.0 and 209.0 kg / ha) was obtained during the single-phase harvesting with pre-desiccation of crops in the phase of 75-80% of brownish heads. In a relatively warm and dry conditions of 2016 seed productivity of tetraploid red clover more depended on the method of harvesting than on its date. On the average over the three years the highest yields of clover seeds (152.1 kg/ha) have been provided by carrying out of a single-phase harvesting with pre-desiccation of crops in the phase of 75-80% of brownish heads at formation of grass stand with the following parameters: the number of heads - 1087 pcs. /m2, seed weight per head - 0.023 g, mass of 1000 seeds - of 2.66 g. The productivity of head had the greatest influence on the formation of seed yield of clover Kudesnik. During the years of investigation only 6-9 pieces of seeds were formed in the head. Laboratory germination of the resulting seeds of red clover was at the level of 90-94%. Seed yield of red clover Kudesnik had the average correlation with the number of seeds in the head r = 0.40), as well as with seeds weight per head (r = 0.48). The energy efficiency ratio at carrying out of a single-phase harvesting with pre-desiccation of crops in the phase of 75-80% of brownish heads was 3.36, profitability level was 234%.